Assessment of Levels of Occupational Exposure to UV-A and UV-C Radiation among Shielded Metal Arc Welders in Accra, Ghana - A. Sawyerr; J.J. Fletcher; J. Amoako; E. Sosu (PPIKSN-BATAN, 2020)
This study attempted to quantify the irradiance levels of ultraviolet A (UV-A) and ultraviolet C (UV-C) from the shielded metal arc welding (SMAW) process to welders in Accra, Ghana. Exposures were assessed via measurements, observations, and interviews. The assessments were done based on safe exposure levels prescribed by recognized international organizations such as the International Commission on Non-Ionizing Radiation Protection (ICNIRP) and the American Conference of Governmental Industrial Hygienists (ACGIH). Results from the measured UV-C irradiance levels EUV-C ranged between 0.16 ± 0.08 W/m2 and 10.46 ± 1.96 W/m2 with its corresponding permissible exposure duration tmax‑UV‑C per day ranging from 5.74 s to 367.35 s. The measured UV-A irradiance levels EUV‑A ranged from 0.88 ± 0.03 W/m2 to 23.72 ± 6.66 W/m2 with its corresponding permissible exposure duration tmax‑UV‑A per day ranging from 421.59 s to 11,363.64 s. The obtained effective irradiance Eeff has a range of 2.08 W/m2 to 28.79 W/m2 with the range of permissible exposure duration tmax per day of 1.04 s to 14.40 s. It was found that the total exposure time of the welders exceeded the permissible exposure durations and that the safety practices among the welders were unsatisfactory.